Succinic acid production from lignocellulosic hydrolysate by Basfia succiniciproducens. (August 2016) - Salvachúa, Davinia; Smith, Holly; St. John, Peter C.; Mohagheghi, Ali; Peterson, Darren J.; Black, Brenna A.; Dowe, Nancy; Beckham, Gregg T.
Highlights: This is the first report of B. succiniciproducens performance in hydrolysate. Succinic acid yields are higher in biomass hydrolysates than pure sugars. The side product lactic acid decreases significantly when using biomass hydrolysate. The bacterium detoxifies furfural and HMF to furfuryl- and HMF-alcohol. A stoichiometric model was utilized to analyze the side product distributions. Abstract: The production of chemicals alongside fuels will be essential to enhance the feasibility of lignocellulosic biorefineries. Succinic acid (SA), a naturally occurring C4-diacid, is a primary intermediate of the tricarboxylic acid cycle and a promising building block chemical that has received significant industrial attention. Basfia succiniciproducens is a relatively unexplored SA-producing bacterium with advantageous features such as broad substrate utilization, genetic tractability, and facultative anaerobic metabolism. Here B. succiniciproducens is evaluated in high xylose-content hydrolysates from corn stover and different synthetic media in batch fermentation. SA titers in hydrolysate at an initial sugar concentration of 60 g/L reached up to 30 g/L, with metabolic yields of 0.69 g/g, and an overall productivity of 0.43 g/L/h. These results demonstrate that B. succiniciproducens may be an attractive platform organism for bio-SA production from biomass hydrolysates.